2021
DOI: 10.3390/vaccines9121479
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Recombinant Lactococcus lactis Strain Expressing VP1 Fusion Protein of Duck Hepatitis A Virus Type 1 and Evaluation of Its Immune Effect

Abstract: With the continuous development of duck farming and the increasing breeding density, the incidence of duck hepatitis A virus type 1 (DHAV-1) has been on the rise, seriously endangering the development of duck farming. To reduce the use of antibiotics in duck breeding, susceptibility risks and mortality, and avoid virulence recovery and immune failure risk, this study aims to develop a new type of mucosal immune probiotics and make full use of molecular biology techniques, on the level of genetic engineering, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Adult ducks are generally resistant to DHAV, and do not display overt clinical signs after infection [ 42 ]. Zhang Yang et al [ 43 ] found DHAV may vertically transmit from breeding ducks to ducklings. Moreover, an epidemiological investigation revealed that many farmers are breeding ducks free-range and lack scientific biosafety measures and appropriate vaccination programmes [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adult ducks are generally resistant to DHAV, and do not display overt clinical signs after infection [ 42 ]. Zhang Yang et al [ 43 ] found DHAV may vertically transmit from breeding ducks to ducklings. Moreover, an epidemiological investigation revealed that many farmers are breeding ducks free-range and lack scientific biosafety measures and appropriate vaccination programmes [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%